ISENTROPIC "SHOCK WAVES" IN NUMERICAL ASTROPHYSICS - Moiseenko, S. G.; Bisnovatyi-Kogan, G. S. (Одеські астрономічні публікації, 2016)
Numerical simulations of the cold supersonic flows in different astrophysical problems meets with the loss of precision difficulty. For to overcome the difficulty it was suggested earlier to use conservation entropy equation instead of energy conservation law. In the paper we analyse quantitatively the error what appears in the shocked flow when isoentropic equations are used. The isentropic equations of gas dynamics can be used only when there are no shocks in the solution or when they are weak and do not significantly affect the flow. The results described here were represented as a talk at the 16-th Gamow Summer School: ”Astronomy and beyond: Astrophysics, Cosmology, Cosmomicrophysics, Astroparticle Physics, Radioastronomy and Astrobiology” 14-20 August, 2016,Odessa,Ukraine. The complete paper is published in Bisnovatyi-Kogan & Moiseenko, 2016.